Tidak Sekadar “Memroyekkan” Kebudayaan: Gagasan Mereformasi Pesta Kesenian Bali - I Ngurah Suryawan (Antropologi Indonesia, 2021)
This article discusses the rationale behind the implementation of the Bali Arts Festival (PKB) since 1979. PKB has become a cultural project for urban middle class intellectuals to reconstruct Balinese culture after the 1965 Tragedy. PKB provides a stage for all components of Balinese society to explore, perform, and preserving the arts as an expression of identity as well as the driving force of the economy. This article argues that PKB represents a culturalism perspective that was developed, one of them, by Ida Bagus Mantra as a technocrat who founded PKB. This culturalism assumes that Balinese people cannot leave their culture, and can only realize themselves within that culture. By culturalism perspective, Balinese’s agency and imagination are subdued and uniformed under the discourse of cultural preservation and cultural tourism. PKB is only used as a cultural project managed by government institutions, in this case the Bali Provincial Culture Office, without responding to social transformation and renewal of the cultural strategy in PKB. PKB should be placed as a Balinese movement of the politics of culture that in the future must reform itself thoroughly.